IUTAM Symposium on Recent Advances in Moving Boundary Problems in Mechanics Proceedings of the IUTAM Symposium on Moving Boundary Problems, Christchurch, New Zealand, February 12-15, 2018 - Gutschmidt, Stefanie; Hewett, James N.; Sellier, Mathieu; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
Many problems in mechanics involve deformable domains with moving boundaries, including fluid-structure interaction, multiphase flows, flows over soft tissues and textiles, or flows involving accretion/erosion to name but a few. The presence of a moving boundary presents considerable challenges when it comes to modelling and understanding the underlying system dynamics. This proceedings volume collects contributions made at the IUTAM Symposium on Recent Advances in Moving Boundary Problems in Mechanics held in Christchurch, New Zealand in February 2018.
Preface -- Can we fabricate that fibre?, by Y.M. Stokes, D.G. Crowdy, H. Ebendorff-Heidepriem, P. Buchak, M.J. Chen -- A Numerical Study on Free Hovering Fruit-fly with Flexible Wings, by Y. Yao, K.S. Yeo, T.T. Nguyen -- Three-dimensional flight simulation with transient moving-aerofoil models, by A. Pons, F. Cirak -- Vortex shedding and flow-induced vibration of two cylinders in tandem, by N. Hosseini, M.D. Griffith, J.S. Leontini -- Flow-induced vibration and energy harvesting using fully-passive flapping foils, by J.S. Leontini, M.D. Griffith, D.L. Jacono, J. Sheridan -- Passive Cavitation Detection During Skin Sonoporation, by J. Robertson, M. Squire, S. Becker -- CFD reconstruction of blood hemodynamic based on a self-made algorithm in patients with acute type IIIb aortic dissection treated with TEVAR procedure, by A. Polanczyk, A. Piechota-Polanczyk, Ch. Neumayer, I. Huk -- The Three Dynamical Regimes of a Droplet Driven by Thermocapillarity, by J.R. Mac Intyre, J.M. Gomba, C.A.Perazzo, P.G. Correa, M. Sellier -- Simulation of the ultrasound-induced growth and collapse of a near-wall bubble, by B. Boyd, S. Becker -- Air flow entrainment of lactose powder: simulation and experiment, by T. Kopsch, D. Murnane, D. Symons -- Oblique Impact of a Droplet on a Textured Substrate, by H. Rashidian, M. Sellier -- Numerical Simulation in Coupled Hydroelastic Problems by using the LS-STAG Immersed Boundary Method, by I.K. Marchevsky, V.V. Puzikova -- On the efficiency of the parallel algorithms in VM2D open source code for 2D flows simulation using vortex methods, by K.S. Kuzmina, I.K. Marchevsky -- A Geometry-Adaptive Immersed Boundary-Lattice Boltzmann Method for Modelling Fluid-Structure Interaction Problems, by L. Xu, L. Wang, F.B. Tian, J. Young, J.C.S. Lai -- Toward the Problem of Low Re Flows Through Linearly Elastic Porous Media, by S. Becker -- Approximate Analytic Solution of the One Phase Stefan Problem for the Sphere, by R.B. Shorten -- Selection Criterion of Stable Mode of Dendritic Growth with n-fold Symmetry at Arbitrary Peclet Numbers with a Forced Convection, by D.V. Alexandrov, P.K. Galenko -- Evolution of a melting sphere in cross flow using an arbitrary mesh topology, by J.N. Hewett, M. Sellier -- Analysis of 3D crack boundary problems by means of the Enriched Scaled Boundary Finite Element Method, by S. Hell, W. Becker -- Analysis of Dynamic Variable Mass and Variable Parameter Systems Applying Semi-Analytic Time-Integration, by H.J. Holl -- Equipartition of modal energy in a stiff vibrating string due to a finite curved boundary obstacle, by A.K. Mandal, P. Wahi -- FEM with Floquet theory for non-slender elastic columns subject to harmonic applied axial force using 2D and 3D solid elements, by E. Clerkin, M. Rieken -- Effects of non-neighbouring members in an array of beams vibrating in fluids, by A.K. Manickavasagam, S. Gutschmidt, M. Sellier.
Keywords: Fluid mechanics; Soft condensed matter; Geotechnical engineering; Engineering Fluid Dynamics; Soft and Granular Matter; Geotechnical Engineering and Applied Earth Sciences